Recurrent Syncope Associated with Lung Cancer - Dingguo Zhang; Liansheng Wang; Zhijian Yang (Case Reports in Medicine)
Syncope is an important problem in clinical practice with many possible causes that might be misdiagnosed. We present an unusual case of syncope, which has a normal chest X-ray. Exercise EKG and coronary angioplasty results confirmed the existence of serious coronary heart disease. The patient was treated with coronary stent transplantation. However, scope occurred again and the elevated tumor makers cytokeratin-19-fragment and neuron-specific enolase revealed the bronchogenic carcinoma, which was confirmed by enhanced CT examination. The treatment of carcinoma by chemotherapy was indeed sufficient for prompt elimination of the syncope symptoms.